Purpose in life and coping strategies: Main associations and moderation by concurrent distress - Angelina R. Sutin; Martina Luchetti; Yannick Stephan; Amanda A. Miller; Antonio Terracciano (PLoS ONE, 2026)
Individuals with more purpose in life tend to report less subjective stress. This association may be due, in part, to the use of more adaptive coping strategies. This research examines how purpose is associated with common coping strategies and whether the relations differ by either sociodemographic factors or current psychological distress. Participants ( N = 1,998) completed a survey that included purpose in life, coping strategies, current symptoms of depression and anxiety, and current feelings of stress. Purpose in life was related to more use of active (β = .36, p < .001) and support (β = .32, p < .001) strategies, and less use of disengaged strategies (β = −.08, p < .001). The associations between purpose and coping were similar across sociodemographic factors (age, sex, race, education). The association with disengaged coping differed by current distress (β interaction = .23, .15, .16, respectively, for depression, anxiety, and stress, all p s < .001): The expected negative association was apparent for participants not in distress, whereas there was a positive association among participants experiencing depression, anxiety, or stress. Purpose in life is associated with coping strategies that can help regulate stress, which may contribute to the lower stress and better psychosocial and health outcomes among people with high purpose.